Markedly increased circulating pyridoxal-5'-phosphate levels in hypophosphatasia. Alkaline phosphatase acts in vitamin B6 metabolism. - Whyte, M P; Mahuren, J D; Vrabel, L A; Coburn, S P (The Journal of Clinical Investigation, 1985)
Markedly increased circulating concentrations of pyridoxal-5'-phosphate (PLP) were found in each of 14 patients representing all clinical forms of hypophosphatasia, an inborn error characterized by deficient activity of the tissue nonspecific (bone/liver/kidney) isoenzyme of alkaline phosphatase (AP). The mean PLP concentration in plasma was 1174 nM (range, 214-3839 nM) in the patients and 57 +/- 26 nM (mean +/- SD) in 38 control subjects. In four affected children, urinary excretion of the PLP degradation product, 4-pyridoxic acid, was unremarkable during consumption of normal quantities of dietary vitamin B6. Our findings identify increased circulating PLP concentration as a marker for hypophosphatasia and provide further evidence that tissue nonspecific AP acts in vitamin B6 metabolism. Tissue nonspecific AP appears to function as an ectoenzyme to regulate extracellular but not intracellular levels of PLP substrate. Performing assays of circulating PLP concentration alone to assess vitamin B6 nutrition may be misleading in disorders associated with altered AP activity.